Feather HSP70: a novel non-invasive molecular marker for monitoring stress induced by heat exposure in broilers. (20th March 2019) - Greene, Elizabeth S; Rajaei-Sharifabadi, Hossein; Dridi, Sami
ABSTRACT: Poultry well-being and economic burden due to heat stress (HS ) are of great importance to the poultry industry. Efficient design and effective evaluation of any strategies to alleviate the adverse effects of HS on poultry production require an accurate measurement of stress. However, current methods for monitoring stress in poultry are less than ideal, as they are invasive or subjective, and therefore variable. Here, we demonstrated that HSP70, the well-established intracellular stress chaperone, is expressed in chicken feather and is responsive to HS, and could therefore be used as a stress marker. Growing feathers were collected from the same bird (Cobb500, n = 9) in the morning (barn temperature 24°C) and afternoon (barn temperature 29.5°C) in the summer (2016 June 21) in Arkansas, USA. In the afternoon, the birds were panting and their core body temperatures were significantly higher compared to the morning time, as illustrated by iButton data thermo-loggers. Concomitantly, blood HSP70 mRNA and feather HSP70 expression (mRNA and protein) were significantly increased in the afternoon compared to the morning time. Similarly, HSP70 protein expression in the duodenum was also significantly higher in the afternoon compared to the morning period. Together, these finding identify feather HSP70 as a novel non-invasive molecular signature that mirrors the intracellular and systemic stress, which can be useful to monitor well-being of chickens and other avian species under different challenges.